Apoptosis-related factors p53, Bcl2, and Bax in neuroendocrine lung tumors. - Brambilla, E. (1996)
Neuroendocrine (NE) lung tumors comprise four classes of progressive aggressiveness for which proliferation and apoptosis rates could both contribute to their distinctive behavior. As p53 mutations may favor escape from apoptosis through changes in Bcl2-Bax expression balance, which are survival and apoptotic genes, respectively, we studied 121 NE lung tumors (16 typical carcinoids (TC), 5 atypical carcinoids (AC), 29 large-cell NE carcinomas (LCNECs), and 71 small-cell lung carcinomas (SCLCs) using immunohistochemistry. We quantified apoptosis by terminal-deoxynucleotidyl-transferase-mediated deoxyuridine triphosphate nick end labeling (TUNEL) in 31 of these cases. There was a significant increase of p53 mutant immunophenotype (defined as immunoreactivity with at least two antibodies for at least 20% of tumor cells) between atypical/typical carcinoids group and the LCNEC/SCLC group (P = 0.0003). There was an inverse correlation (P < 0.0001) between the scores of Bax and Bcl2 expression in individual tumors and a significant inversion of the Bcl2. Bax ratio between low-grade (typical and atypical carcinoids) and high-grade (LCNECs and SCLCs) tumors with a predominant Bax expression in the first group and predominant Bcl2 expression in the second. Whereas carcinoids had variable apoptotic indexes, LCNECs had high indexes (1.3 to 6.8%), Bcl2 overexpression, Bax down-regulation, and Bcl2.Bax ratio > 1 correlated with lower apoptotic index in both LCNEC and the pool of LCNECs and SCLCs (P < 0.05) and a lower survival rate in the group of atypical and typical carcinoids and LCNECs (P < 0.002). The highest levels of Bcl2 expression and Bcl2.Bax ratios were associated with p53 mutant immunophenotype (P = 0.02). Our results suggest that aggressiveness in NE lung tumors could be linked, in addition to proliferation, to apoptosis-related factors.